On training of jurists of the 21st century (a more or less utopian altarpiece with Bologna as background) - Martín Rebollo, Luis (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The present work is a personal reflection about the training of jurists at University; about what can and should be taught and learned. The author defends that more than specific knowledge, the important thing is to learning how to move among plural rules, assuming the values that underlie them, as well as understanding the main or general aspects, learning how to reason and to present orally or in writing a proposition or a thought. This subjective perspective is conditioned by the target to be achieved and by the purposes of teaching (whether it is purely professional or more general). The training is conditioned also by the environment: the organization of the university as well as the study plans, but, above all, by who the professors are, which opens a subsequent debate about the selection of the professors and their training. About this question the author is critical and, to a certain point, resigned.
Keywords: training of new jurists; context of the University; Bologna Plan; purposes of the university teaching of Law